Sternberg's Diagnostic Surgical Pathology.vol.1 - Mills, Stacey E (Lippincott Williams and Wilkins, 2004)
Completely updated, the Fourth Edition of this standard-setting two-volume reference presents the most advanced diagnostic techniques and the latest information on all currently known disease entities. More than 90 preeminent surgical pathologists offer expert advice on the diagnostic evaluation of every type of specimen from every anatomic site. The Fourth Edition contains 3,494 full-color photographs, of which over 1,100 are new. This edition has three distinguished new editors--Joel K. Greenson, MD, Victor E. Reuter, MD, and Mark H. Stoler, MD--and many new contributors. Updates include new immunohistochemical markers for lymphoid neoplasms, current nomenclature for lymphoid tumors, and state-of-the-art molecular genetic tests. A bound-in CD-ROM contains all the images from the book, downloadable to PowerPoint presentations. \"Doody\'s Core Titles™ 2009.\"
Keywords: diagnostické metody; Diagnostic Techniques, Surgical; Pathology, Surgical; patologie; chirurgická patologie; diagnostické techniky chirurgické